Sun Safe Workplaces: Effect of an Occupational Skin Cancer Prevention Program on Employee Sun Safety Practices. Issue 11 (November 2018) - Walkosz, Barbara J.; Buller, David; Buller, Mary; Wallis, Allan; Meenan, Richard; Cutter, Gary; Andersen, Peter; Scott, Michael
Abstract : Objective: Occupational skin cancer prevention is a priority because outdoor workers are exposed to high levels of ultraviolet radiation, the primary risk factor for skin cancer. Methods: A 2-year follow-up assessment of the impact of Sun Safe Workplaces (SSW), a workplace sun safety program that promoted policy adoption and education, on employee sun safety behavior was conducted. Sixty-three of 98 local government organizations from the original study participated. Results: Outdoor workers ( n = 1724) completed surveys on personal sun protection practices. Employees' sun protection improved statistically significantly in the intervention group receiving the SSW program. SSW's effect was mediated by the number of workplace actions to implement elements of the policy, including sun protection messages and equipment and employee reports of sun safety training. Conclusion: Policy promotion is a feasible approach to occupational skin cancer prevention.